Analisis Pengaruh Variasi Pendinginan Terhadap Nilai Kekerasan dan Struktur Mikro Baja ST 42 Hasil Pengelasan SMAW - Wiratmaja, I Gede; Nugraha, I Nyoman Pasek; Mahayoga, I Kadek Alit (Nusantara of Engineering (NOE), 2025)
The purpose of the research is to find out how the effect of cooling media variations of air, water, and SAE 40 oil on the level of hardness and microstructure of SMAW welding results on ST 42 steel material. The type of research used in this research is experimental research with Quantitative methods. The results showed that the variation of cooling media had a significant effect on the hardness and microstructure of the SMAW welding results. The highest average hardness with water cooling media in the weld metal area was 125.080 Kgf/mm², the HAZ area was 111.375 Kgf/mm², the parent metal area was 129.429 Kgf/mm² while the lowest hardness with air cooling media in the weld metal area was 93.205 Kgf/mm², the HAZ area was 99.806 Kgf/mm², the parent metal area was 121.893 Kgf/mm². Furthermore, the results of testing the microstructure of ST 42 steel from SMAW welding with water cooling media in the HAZ (Heat Affected Zone) area show more and denser pearlite grains, this shows a strong correlation between the amount of distribution and density of pearlite grains with an increase in hardness of ST 42 steel material from SMAW welding, especially with water cooling media.